2014
DOI: 10.15288/jsad.2014.75.1023
|View full text |Cite
|
Sign up to set email alerts
|

Does Sexual Self-Concept Ambiguity Moderate Relations Among Perceived Peer Norms for Alcohol Use, Alcohol-Dependence Symptomatology, and HIV Risk-Taking Behavior?

Abstract: ABSTRACT. Objective: The current study examines the relation between peer descriptive norms for alcohol involvement and alcoholdependence symptomatology and whether this relation differs as a function of sexual self-concept ambiguity (SSA). This study also examines the associations among peer descriptive norms for alcohol involvement, alcohol-dependence symptomatology, and lifetime HIV risk-taking behavior and how these relations are infl uenced by SSA. Method: Women between ages 18 and 30 years (N = 351; M = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Results suggest that individuals with SSA may use alcohol as a situational means to regulate negative affect, particularly aversive selffocus, and as a result, they may suffer more negative consequences as a result of their alcohol use. Indeed, previous work (Talley, Brown, Stevens, & Littlefield, 2014) found that individuals who are higher in SSA report a greater number of potential symptoms of alcohol dependence. Taken together, the current report is one of the first studies to provide causal evidence of an identity-related contributor that may lead to increased alcohol consumption among sexual minority individuals who acknowledge SSA.…”
Section: Discussionmentioning
confidence: 97%
“…Results suggest that individuals with SSA may use alcohol as a situational means to regulate negative affect, particularly aversive selffocus, and as a result, they may suffer more negative consequences as a result of their alcohol use. Indeed, previous work (Talley, Brown, Stevens, & Littlefield, 2014) found that individuals who are higher in SSA report a greater number of potential symptoms of alcohol dependence. Taken together, the current report is one of the first studies to provide causal evidence of an identity-related contributor that may lead to increased alcohol consumption among sexual minority individuals who acknowledge SSA.…”
Section: Discussionmentioning
confidence: 97%
“…The development of the SSA scale utilized data from a study examining how aspects of women’s sexuality may influence their health risk behavior (e.g., Talley et al, 2014; Talley et al, 2015). Importantly, the calibration sample was recruited for the expressed purpose of adapting and validating this measure of SSA.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed framework highlighted the importance of identity-related characteristics, including sexual self-concept ambiguity, in contributing to the physical and mental health outcomes of sexual minority-identified persons. Notably, recent empirical work has supported hypothesized associations between the proposed SSA scale and alcohol misuse, risky sex, and suicidal ideation (e.g., Talley, Brown, Stevens, & Littlefield, 2014; Talley et al, 2015). Given previous findings in the extant literature, as well as pertinent theoretical models (see Meyer, 2003; Talley & Littlefield, 2014), we sought to provide evidence for criterion validity by showing that higher levels of SSA will be associated with greater alcohol misuse, depression symptoms, and anxiety symptoms.…”
mentioning
confidence: 95%
“…Specifically, because little attention has been paid to predictive relationships between social norms, the perceived benefits of drinking, alcohol identity and alcohol dependence, this study contributes to the literature by integrating findings in the social norms and alcohol dependence literatures. In particular, although a study identified a direct relationship between social norms and alcohol dependence (Talley et al , 2014), little attention has been paid to the mediating factors in the relationship between social norms and alcohol dependence. This study demonstrated that alcohol dependence is influenced by social norms through alcohol identity and the perceived benefits of drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on alcohol use behavior that are based on social learning theory have also demonstrated that social norms directly affect alcohol dependence (Talley et al , 2014) and the perceived benefits of drinking (Epstein et al , 2008). However, despite popular interest in the topic, the mechanism underlying (mediating factors) the relationship between social norms and alcohol dependence has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%